MENDESAIN HYBRID LEARNING DENGAN MODEL PENGEMBANGAN ADDIE UNTUK PELAJARAN PENDIDIKAN AGAMA - Natalis Sukma Permana (Bahasa Indonesia, 2022)
This paper aims to explain how to design Catholic religious education learning activities using the Hybrid Learning method. The importance of learning design is first to improve the quality of education and make it easier for students to learn. When you want to improve the quality of Catholic religious education, what needs to be considered is the quality of learning. During the COVID-19 pandemic situation, to overcome the learning loss dilemma that occurs at the education level, hybrid learning is one method that can be taken to carry out learning activities. Hybrid/mixed learning refers to a combination of online learning and conventional (face-to-face) learning. Innovations that can be made in Hybrid Learning combine several forms, for example, Flipped classroom, flex model, rotation model, enriched model, anchor model. This innovation needs to be done to learn. Catholic religious education is more fun to motivate and facilitate students in learning. Determine the form of hybrid learning can be done by following the steps of learning development with the ADDIE model. The development procedure goes through the steps of analysis, design, development, implementation, and evaluation. The development of hybrid learning using the ADDIE model is expected to be able to produce a hybrid learning design that is per the learning objectives and characteristics of the students.